Differential dendritic cell‐mediated activation and functions of invariant NKT‐cell subsets in oral cancer. (8th April 2014) - Singh, AK; Gaur, P; Shukla, NK; Das, SN
Abstract : Objectives: Invariant natural killer T (iNKT) cells are unique subset of glycolipid‐reactive T lymphocytes with potent antitumour characteristics. This study was planned to understand Th‐like cytokine profiles of iNKT‐cell subsets and modulation of their functions in response to glycolipid ligand and tumour cell lysate (TL). Subjects and Methods: Cytokine profile of iNKT‐cell subsets was evaluated from the peripheral blood of eight oral squamous cell carcinoma (OSCC) patients by flow cytometry and enzyme‐linked immunosorbent assay (ELISA), while antitumour activity of iNKT cells was measured by methyl tetrazolium salt assay. Results: CD4 + (CD4 + CD8 − ) iNKT subset from OSCC patients showed significant ( P  < 0.01) expansion and higher IL‐4 production following activation with α ‐GalCer‐pulsed DCs, while CD4 − CD8 − double negative (DN) and CD8 + (CD4 − CD8 + ) iNKT subsets produced IFN‐ γ predominantly. iNKT cells showed significantly ( P  = 0.02) increased secretion of IFN‐ γ and enhanced cytotoxicity to KB and SCC‐4 tumour cells in response to α ‐GalCer and TL‐pulsed DCs. Conclusion: It appears that mutual balance/ratio of iNKT subsets may be important for their effector functions. Selectively expanded DN and CD8 + iNKT cells with α ‐GalCer and TL may be a better candidate vaccine for iNKT‐cell‐based adoptive cancer immunotherapy.